2019
DOI: 10.4103/sjg.sjg_421_18
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B care pathway in Saudi Arabia: Current situation, gaps and actions

Abstract: Hepatitis B virus (HBV) infection remains a public health problem worldwide. In this review, we aim to assess the current situation of the HBV care pathway in the Kingdom of Saudi Arabia (KSA), identify gaps/barriers therein, and recommend initiatives to be taken to improve the management of such patients. Towards this end, a literature search was conducted in PubMed and free Internet searches. Interviews with individuals and focus group discussions were held with HBV experts in KSA. Although significant impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 35 publications
0
29
2
Order By: Relevance
“…14 A systematic review and meta-analysis for 36 published studies in Saudi Arabia from 1965 to 2013 found a 3.2% prevalence of HBV, which was slightly lower than the worldwide prevalence of 3.6%. 15 In Saudi Arabia, obesity and instances of being overweight are increasing with an overall rate of 35.5%. 16,17 The region of Riyadh is considered one of the most highly affected areas with obesity in Saudi Arabia, with a 35% prevalence of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…14 A systematic review and meta-analysis for 36 published studies in Saudi Arabia from 1965 to 2013 found a 3.2% prevalence of HBV, which was slightly lower than the worldwide prevalence of 3.6%. 15 In Saudi Arabia, obesity and instances of being overweight are increasing with an overall rate of 35.5%. 16,17 The region of Riyadh is considered one of the most highly affected areas with obesity in Saudi Arabia, with a 35% prevalence of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Since HBV and HCV are endemic in KSA, there are numerous reports describing their prevalence, clinical characteristics, and sero-epidemiology. 2 However, only few reports describe HBV or HCV co-infections in HIV-positive people in the KSA ( Table 1 ). HCV infection has been frequently reported to be the most dominant co-infection in HIV-positive individuals followed by HBV.…”
Section: Co-infections Involving Hiv and Viral Hepatitis In The Kingdmentioning
confidence: 99%
“…Similarly, hepatitis B vaccination has also significantly reduced the HBV infection rates in KSA. [ 51 52 53 54 ] In fact, a recent review of the hepatitis B care pathway in the country demonstrated that significant improvements had been made in the last decades. These efforts result in an estimated current HBV prevalence of approximately 1.5% in the KSA.…”
Section: Preventionmentioning
confidence: 99%
“…These efforts result in an estimated current HBV prevalence of approximately 1.5% in the KSA. [ 54 ] Although there are no formal studies on the outcomes of hepatitis B vaccination on HCC incidence, there are some suggestions that the HBV-related HCC incidence has reduced. Three newer studies done between 2011 and 2014 found higher HCV-related HCC rates compared to HBV,[ 24 55 56 ] as opposed to older studies between 1990 and 2004, where HBV was the predominant HCC etiology.…”
Section: Preventionmentioning
confidence: 99%
See 1 more Smart Citation